2002
DOI: 10.1159/000048251
|View full text |Cite
|
Sign up to set email alerts
|

Acridine Orange Excited by Low-Dose Radiation Has a Strong Cytocidal Effect on Mouse Osteosarcoma

Abstract: The study was conducted to clarify the cytocidal effect of combination therapy consisting of administration of acridine orange (AO), which is a photosensitizer, and radiation therapy using in vitro and in vivo mouse osteosarcoma models. The results revealed that AO combined with low-dose X-ray irradiation of about 1–5 Gy had a strong cytocidal effect on the cultured mouse osteosarcoma cells regardless of their chemosensitivity, and that this combination therapy inhibited growth of the in vivo mouse osteosarcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 26 publications
1
66
0
Order By: Relevance
“…Since the beginning of the 20th century, acridine family compounds have been well known for their pharmacological properties. 19 Acriflavine hydrochloride has been used as a topical antiseptic, and acridine derivatives have been used for antimalarial and anticancer therapy. Pharmacological properties of these agents are closely related to reversible binding of these compounds to DNA regulatory enzymes.…”
Section: Rapid Fluorescent Dyes Suitable For Ex Vivo Imagingmentioning
confidence: 99%
“…Since the beginning of the 20th century, acridine family compounds have been well known for their pharmacological properties. 19 Acriflavine hydrochloride has been used as a topical antiseptic, and acridine derivatives have been used for antimalarial and anticancer therapy. Pharmacological properties of these agents are closely related to reversible binding of these compounds to DNA regulatory enzymes.…”
Section: Rapid Fluorescent Dyes Suitable For Ex Vivo Imagingmentioning
confidence: 99%
“…Furthermore, we found that low-dose X-ray irradiation at 5 Gy after exposure to AO of a mouse osteosarcoma yielded the same strong cytocidal effect in vitro and in vivo as that of by AO-PDT [22]. This radiation effect with AO was independently demonstrated by an Iowa University group in the USA in 2006 [23].…”
Section: Ao-pdt and Ao-rdtmentioning
confidence: 59%
“…In an in-vivo study carried out using a mouse osteosarcoma model, tumor growth was significantly inhibited by AO injection at 10 mg/kg into the peritoneum followed by light illumination of the tumor. This result suggested the potential usefulness of AO for photodynamic therapy in patients with musculoskeletal sarcomas [20][21][22].…”
Section: Ao-pdt and Ao-rdtmentioning
confidence: 72%
See 1 more Smart Citation
“…Consequently, this in vivo study was conducted. Previously, we reported that the intraperitoneal administration of AO at 10 mg/ kg followed by blue light excitation inhibited the tumor growth of osteosarcoma developing from a different cell line (MOS) than LM8 in vivo (14,15,18,19). Recently, we also found that the intravenous administration of AO at 1.0 mg/kg is useful for PDD of mouse osteosarcomas in nude mice.…”
Section: Discussionmentioning
confidence: 98%